Gender differences in Parkinson's disease: A clinical perspective. (2nd July 2017) - Georgiev, D.; Hamberg, K.; Hariz, M.; Forsgren, L.; Hariz, G.‐M.
Abstract : Available data indicate that there are gender differences in many features of Parkinson's disease (PD). Precise identification of the gender differences is important to tailor treatment, predict outcomes, and meet other individual and social needs in women and men with PD. The aim of this study was to review the available clinical data on gender differences in PD. Original articles and meta‐analyses published between 1990 and 2016 systematically exploring gender differences in PD were reviewed. There is slight male preponderance in incidence and prevalence of PD. PD starts earlier in men. Women tend to be more prone to develop tremor‐dominant PD but are less rigid than men. Motor improvement after deep brain stimulation is equal in both sexes, but women tend to show better improvement in activities of daily living. Furthermore, women with PD show better results on tests for general cognitive abilities, outperform men in verbal cognitive tasks, show more pain symptoms, and score higher on depression scales. It seems, however, that the differences in cognition, mood, and pain perception are not disease specific as similar gender differences can be found in healthy subjects and in other neurological conditions. Despite PD being the most frequently studied movement disorder, studies investigating gender differences in PD are still scarce with most of the studies being cross‐sectional. Good‐quality, prospective, longitudinal studies analyzing gender differences in PD and comparing them to matched healthy controls are needed in order to properly address the issues of gender differences in PD.